Characterization and identification of indices morphometric zoometric of a pure White Orejinegro (BON) creole cattle herd, in Pacho (Cundinamarca) (Revista Sistemas de Producción Agroecológicos, 2014)
This research was conducted in Pacho, Cundinamarca, Colombia, where cows of the creole breed Blanco Orejinegro were evaluated with the help of a metric tape and zoometric gad. These measures permitted the elaboration of a correlation matrix defining that these animals correspond to a harmonic model. This way, we characterized the morphometrics characteristics of the BON breed. According to the correlation analysis, this study or the present work found that in the 88, 23% of de cases exist a positive correlation between the variables. Therefore, it is defined that these animals of the BON breed have a high degree of harmonicity in their morphostructural model.
Keywords: creole; Blanco Orejinegro; morfometric; harmonic model; index morphometric